Green Innovation Sebagai Pemoderasi: Determinan Pengungkapan Environmental, Social, Governance - Ni Putu Ayu Astiti Mustika Astari; I Gusti Ayu Purnamawati; Desak Nyoman Sri Werastuti (Owner : Riset dan Jurnal Akuntansi, 2025)
Environmental, Social, and Governance (ESG) is an important indicator in assessing a company's commitment to sustainability, as well as a strategic consideration in socially responsible investment. This study aims to test and analyze the effect of Enterprise Risk Management, Financial Performance, and Foreign Ownership on Environmental, Social, and Governance disclosure with Green Innovation as a moderating variable. The approach used in this study is a quantitative approach with multiple linear regression analysis on companies that are consistently listed in the ESG Leaders Index and the SRI-KEHATI Index with annual report periods and sustainability reports in 2020-2023. The purposive sampling technique was used to obtain 17 companies with a total of 68 data in 4 years and analyzed using STATA 15.0 software. This study uses the Moderated Regression Analysis (MRA) test. This study shows that Enterprise Risk Management (ERM), Net Profit Margin (NPM), and foreign ownership have various effects on Environmental, Social, and Governance (ESG) disclosure. NPM has a significant positive effect, while ERM and foreign ownership are not significant. Green Innovation (GI) fails to moderate the relationship between ERM, Tobin's Q, and foreign ownership on ESG, and actually weakens the relationship between NPM and ESG. These results confirm that internal factors such as green innovation have not been optimized, while external factors and short-term strategies are more dominant in driving ESG transparency in Indonesian companies.